Setting up Pharmaceutical Laboratory Business in China: An Exploratory Study - Chua, Victor Chin Hong (2009)
This project is trying to explore the possibility of Pharmaceutical Division, Applied Sciences Group (ASG), a division in Health Sciences Authority (HSA), Ministry of Health in setting up a pharmaceutical laboratory with office in People’s Republic of China. There are several objectives in doing so but the main objective is to generate revenues in a new booming economy in Asia - China.